Polar cap patches and auroral blobs observed with Antarctic HF radars: Preliminary results - Ogawa, Tadahiko; Nishitani, Nozomu; Pinnock, Mike; Sato, Natsuo; Yamagishi, Hisao; Yukimatu, Akira Sessai (National Institute of Polar Research, 1998)
P(論文) We present preliminary results of the Antarctic HF radar observations of decameter-scale irregularities associated with polar cap patches and auroral blobs in the southern high latitude ionosphere. Somewhat surprisingly, patches appear even under northward interplanetary magnetic field (IMF) conditions. These patches seem to have been transported from the dayside cusp into the polar cap, although we need more data analysis to confirm this conclusion. The blobs, clearly detected with the Halley radar, in the evening auroral zone seem to be well explained by previous simulations that calculated the time evolution of a patch initially located in the polar cap. departmental bulletin paper